PEMANFAATAN BUNGA TAPAK DARASEBAGAI ALTERNATIF PEMBUATAN INDIKATOR pH ASAM‐BASA - Muhammad Hizbul W., Eko Yuliyanto, dan Martina Retnoyuanni (Pelita - Jurnal Penelitian Mahasiswa UNY, 2009)
AbstractThis research aims to know 1) the process of making acid‐base indicator, 2) the way to use it, 3)the changing of colour caused by this indicator, 4) the way to make pH trajectory from tapak daraflower.This research was conducted in a two‐stage method; they are the making of pH indicator in theform of liquid and paper and that of pH trajectory as pH indicator.The result of the research shows that pH indicator from tapak dara flower in the form of liquidand paper shows a different colour in the condition of acid and base. This indicator can be used todetermine pH solution by matching the colour formed in the solution and that in pH trajectory. Theconclusions of this research are 1) liquid indicator is produced from the extraction of tapak dara flower,this extract is from the soaking of this flower with alcohol 70% and paper indicator is made by plungingfilter paper into this extract; 2) liquid indicator is used by dropping it into the solution that will be testedits pH and paper indicator by plunging the paper into the solution; 3) liquid and paper pH indicator fromtapak dara flower shows the changing of colour in the acid and base condition being observed; and 4) pHtrajectory is made by observing the changing of colour that is made its trajectory.Key Words: pH indicator, tapak dara flower, pH trajectory